2018
DOI: 10.1128/jb.00240-18
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mycobacterium Proteins with Lipid Droplets

Abstract: is a global pathogen of significant medical importance. A key aspect of its life cycle is the ability to enter into an altered physiological state of nonreplicating persistence during latency and resist elimination by the host immune system. One mechanism by which facilitates its survival during latency is by producing and metabolizing intracytoplasmic lipid droplets (LDs). LDs are quasi-organelles consisting of a neutral lipid core such as triacylglycerol surrounded by a phospholipid monolayer and proteins. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 61 publications
3
34
0
Order By: Relevance
“…The proteomic study revealed that PspA was also one of the LD major proteins same as other bacteria, suggesting that the E coli TOP10 has the ability to form LDs and the LDs are conserved in Bacteria domain. Additionally, a recent study reports that PspA targets bacterial LDs using an amphipathic α-helix [50], which is similar with the pattern of mammalian LD protein localization [6]. Furthermore, current study also found that PspA was conserved from bacteria, archaea, to eukaryotes (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The proteomic study revealed that PspA was also one of the LD major proteins same as other bacteria, suggesting that the E coli TOP10 has the ability to form LDs and the LDs are conserved in Bacteria domain. Additionally, a recent study reports that PspA targets bacterial LDs using an amphipathic α-helix [50], which is similar with the pattern of mammalian LD protein localization [6]. Furthermore, current study also found that PspA was conserved from bacteria, archaea, to eukaryotes (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…PspA from E. coli can localize on the LDs in Mycobacterium smegmatis [50]. These results suggest that PspA is not only a widespread protein existing in Bacteria domain, but also a universal LD protein in bacteria.…”
Section: The Lipid Droplets Are Conserved and Inheritable In Bacteriamentioning
confidence: 77%
“…In phenotype A, bright red fluorescence was found within the compartments surrounded by EGFP-HBHA ( Figure 2D ), indicating that these structures could correspond to ILI for TAG storage. This second localization is supported by the recent description of M. smegmatis HBHA homolog (MSMEG_0919) as a major protein associated with ILI by proteomic analysis of isolated ILI ( Armstrong et al, 2018 ).…”
Section: Resultsmentioning
confidence: 55%
“…Our data do not support this hypothesis and show that, in addition to its adhesin properties, HBHA has conserved a role in ILI accumulation and maturation. Recently, the M. smegmatis HBHA homolog (MSMEG_0919) has been found as the major ILI-associated protein ( Armstrong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the additional upregulated genes in hbhR::Tn is pspA . Recent proteomic analyses of ILI‐associated proteins in M. smegmatis showed that PspA and HBHA are the two most abundant proteins (Armstrong et al , ), suggesting that co‐regulation of these genes is paralleled with similar function of their gene products. Carbon storage is an important trait of M. tuberculosis to reach a dormant state.…”
Section: Discussionmentioning
confidence: 99%